The UK as a medium maritime power in the 21st century logistics for influence - Martin, Christopher (Palgrave Macmillan, 2016)
This book argues that the UK, as a post-modern globalised state, will require means to have influence over events and opponents that threaten the UK's interests in the 21st century, and that its means is the Royal Navy.